Pulse oximetry reference values at high altitude. Issue 3 (March 1992) - Lozano, J M; Duque, O R; Buitrago, T; Behaine, S
Abstract : Pulse oximetry is becoming popular for measuring oxygen saturation of haemoglobin in paediatric patients. There are no reference values for children living at high altitudes, and the aim of this study was to determine the values of oxygen saturation of haemoglobin in healthy children in Bogota (2640 m above sea level). The saturation was determined in 189 children aged 5 days to 24 months with a Nellcor N10 oximeter. Mean values and 95% confidence intervals (CI) were calculated. Analysis of variance was used for assessing the differences in saturation with age and physiological status. The values were normally distributed with a mean (SD) of 93.3 (2.05)% and 95% CI of 93.0% to 93.6%. There were no clinically important differences in the oxygen saturation of haemoglobin in the range of ages included. The mean saturation in sleeping children was significantly lower than that during other physiological states (91.1% v 93.3%) but the difference was not clinically important. As expected, the values for the oxygen saturation of haemoglobin in the children studied were lower than those reported from children living at sea level. These estimates can be used for interpreting results of the oxygen saturation in haemoglobin in children from Bogota and other cities located at a similar altitude.